Hirohito and the making of modern Japan - Bix, Herbert P. (Perennial, 2000)
In this groundbreaking biography of the Japanese emperor Hirohito, Herbert P. Bix offers the first complete, unvarnished look at the enigmatic leader whose sixty-three-year reign ushered Japan into the modern world. Never before has the full life of this controversial figure been revealed with such clarity and vividness. Bix shows what it was like to be trained from birth for a lone position at the apex of the nation's political hierarchy and as a revered symbol of divine status. Influenced by an unusual combination of the Japanese imperial tradition and a modern scientific worldview, the young emperor gradually evolves into his preeminent role, aligning himself with the growing ultranationalist movement, perpetuating a cult of religious emperor worship, resisting attempts to curb his power, and all the while burnishing his image as a reluctant, passive monarch. Here we see Hirohito as he truly was: a man of strong will and real authority.